An in vitro cell-based potency assay for pharmaceutical type A botulinum antitoxins. Issue 52 (19th December 2017) - Torgeman, Amram; Diamant, Eran; Levin, Lilach; David, Alon Ben; Epstein, Eyal; Girshengorn, Meni; Mazor, Ohad; Rosenfeld, Ronit; Zichel, Ran
Abstract: Botulism therapy relies on passive immunization with antitoxin. The mouse neutralization test is the only pharmacopeia assay to measure the potency of antitoxin preparations. Herein, we present an in vitro cell-based assay for the measurement of pharmaceutical type A antitoxin potency. Accuracy, reproducibility and compatibility with the mouse bioassay were demonstrated using different batches of standard antitoxin and toxin preparations. The established assay may substantially reduce the use of laboratory animals in the process of pharmaceutical antitoxin production.